Influence of Method, Duration and Norms of Application of Logon Minefield Bentonite Mud on the Amount of Nutrients in the Soil - Turakulov, Dilmurod Abdulvositovich (RA Journal of Applied Research, 2021)
The article discusses the impact of the application of bentonite sludge from the Logan deposit in different methods, terms and standards on the nutrients in the soil in the conditions of meadow saline, moderately saline soils of Central Fergana.As a result of application of Logan bentonite mud under autumn plowing at the rate of 1.5-3.0 t / ha per year, in three years in the driving layer of the soil humus 0.003-0.007%, total nitrogen 0.002-0.006%, phosphorus 0.005-0.015%, potassium 0.012-0.030 % increase and reports of improved agrochemical properties.